Progress and prospects of targeted therapy and immunotherapy for urachal carcinoma - Zheng, Yang; Peng, Heling; Hu, Xu; Ou, Yong; Wang, Dong; Wang, Han; Ren, Shangqing (Frontiers in Pharmacology, 2023)
Introduction: Urachal carcinoma (UrC) is a rare and aggressive disease. Systematic chemotherapy shows limited efficacy in patients with advanced disease, while targeted therapy and immunotherapy may provide a reasonable alternative for specific populations. The molecular pattern of colorectal cancer (CRC) have recently been identified; this understanding has significantly influenced the clinical management of CRC in terms of molecular-targeted therapy. Although some genetic alterations have been associated with UrC, there is still no systematic overview of the molecular profile of this rare malignancy. Methods: In this review, we comprehensively discuss the molecular profile of UrC and further identify potential targets for the personalized treatment of UrC as well as immune checkpoint inhibitors that represent underlying biomarkers. A systematic literature search was carried out by searching the PubMed, EMBASE, and Web of Science databases to identify all literature related to targeted therapy and immunotherapy in urachal carcinoma from inception to February 2023. Results: A total of 28 articles were eligible, and most studies included were case report sand retrospective case series. Furthermore, 420 cases of UrC were identified to analyze the association between mutations and UrC. The most commonly mutated gene in UrC was TP53 with the prevalence of 70%, followed by KRAS mutations in 28.3%, MYC mutations in 20.3%, SMAD4 mutations in 18.2% and GNAS mutations in 18%, amongst other genes. Discussion: The molecular patterns of UrC and CRC are similar yet distinct. Notably, targeted therapy, especially EGFR-targeting therapy, might provide curative efficacy for patients with UrC by applying specific molecular markers. Additional potential biomarkers for the immunotherapy of UrC are mismatch repair (MMR) status and PD-L1 expression profile. In addition, combined regimens featuring targeted agents and immune checkpoint blockers might increase antitumor activity and exert better efficacy in UrC patients with specific mutational burden.